Integrating Sketchup-Based 3d Modeling Into Graphic Design and Architectural Education: Enhancing Visual Thinking and Creative Skills - Muldiyana, Muldiyana (Peneliti.net, 2026)
This study examines the pedagogical function of SketchUp-based 3D modeling in enhancing visual communication, creativity, and spatial literacy among students in graphic design and architectural visualization programs. In the evolving domain of digital design education, SketchUp functions as an accessible and intuitive platform that merges technical modeling with conceptual ideation, enabling learners to convert imagination into visual representation. This study utilized a qualitative-descriptive methodology, collecting data from classroom observations, student comments, and project assessments in design and architecture classes to evaluate SketchUp's influence on learning engagement and skill enhancement.The results show that SketchUp fosters interactive learning settings that enhance active experimentation, exploration, and spatial reasoning. In contrast to traditional two-dimensional drawing methods, SketchUp offers instant visual feedback, thereby improving students' understanding of design and their problem-solving skills. Participants exhibited heightened enthusiasm, assurance, and digital competence, illustrating SketchUp's capacity to foster collaborative, project-oriented learning in alignment with constructivist educational ideas.The pedagogical incorporation of SketchUp fosters a synergy between creative ideation and technical proficiency, so enhancing the educational experience and encouraging students to critically interact with design concepts. Identified challenges encompass insufficient technical skill among novices and the necessity for curricular integration frameworks to enhance digital modeling instruction. Overall, this research concludes that SketchUp-based 3D modeling strengthens both cognitive and practical aspects of design education, preparing students to become adaptive and digitally literate professionals ready for the demands of creative industries.